1986
DOI: 10.2334/josnusd1959.28.287
|View full text |Cite
|
Sign up to set email alerts
|

Basic studies on visible light-curing resin as a denture base. Part 4. Its strength in the repair of fractured parts of heat-curing denture base resin.

Abstract: The authors have hitherto reported a series of basic studies on visible light

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 1 publication
0
9
1
Order By: Relevance
“…One of the reasons for this unfavourable phenomenon is the limited flexural strength of auto‐polymerising acrylic resin, which is lower than that of heat‐polymerising acrylic resin 9 . Previous studies have shown that the flexural strength was within the range 18–95% 1,2,12,14,21,28 and 19–55% for repairs auto‐polymerising and VLC resins, respectively, of the intact heat‐polymerising resin 21,24 . In contrast to the literature, the findings of the present study showed that the overall flexural strengths of specimens repaired with auto‐polymerising resin and VLC resin were 24.5 and 39.0%, respectively, of the original strength of their intact form.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…One of the reasons for this unfavourable phenomenon is the limited flexural strength of auto‐polymerising acrylic resin, which is lower than that of heat‐polymerising acrylic resin 9 . Previous studies have shown that the flexural strength was within the range 18–95% 1,2,12,14,21,28 and 19–55% for repairs auto‐polymerising and VLC resins, respectively, of the intact heat‐polymerising resin 21,24 . In contrast to the literature, the findings of the present study showed that the overall flexural strengths of specimens repaired with auto‐polymerising resin and VLC resin were 24.5 and 39.0%, respectively, of the original strength of their intact form.…”
Section: Discussioncontrasting
confidence: 97%
“…Fifty‐four specimens were prepared with dimensions of 65 mm × 10 mm × 2.5 mm 12,21–24 by means of conventional moulding. Heat‐polymerising acrylic resin (Table 1) was mixed with a powder/liquid (P/L) ratio of 24 g per 10 ml for 60 s according to manufacturer’s recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…The adhesive failures originated by the two mechanical tests could be attributed to the butt joint 3,23,26 . Several factors have been described as capable of affecting the strength of the repaired acrylic resin, such as the contour of the butt joint surface, 10,29 pretreatment of the surfaces with monomer, 38 and longer water storage periods 6,39 . The butt joint was chosen because it requires less preparation and a joint area that is more homogeneous than 45° bevel joint, round joint, or edge joint 9,14,29 …”
Section: Discussionmentioning
confidence: 99%
“…This reveals that repairing techniques for the fractured denture need to be further explored. Factors such as materials used for repairs ( Anderson, 1976; Andreopoulos & Polyzois, 1994), joint surface contour ( Beyli & von Fraunhofer, 1980; Ward et al , 1992 ; Ishigamik & Maeda, 1993), joint surface gap ( Ishigamik, Shirane & Aoyama, 1986; Fellman, 1989; Ishigamik & Maeda, 1993) and joint surface treatment ( Shen, Colaizzi & Birns, 1984; Vallittu, Lassila & Lappalainen, 1994) have been studied. However, a very important factor, the deleterious effect from oral fluids, appears to have been ignored.…”
Section: Introductionmentioning
confidence: 99%